Distance of interproximal separation according to time, using two types of elastomeric separators - Ampuero Martinich, Carla Maria (2019)
Objective: To determine the distance of iterproximal separation according to time, using two types of elastomeric separators in patients of the Center Dental of the University of San Martín de Porres. Material and Methods: was an observational, analytical, prospective and longitudinal study, in which a single examiner evaluated in 120 nanalysis units the mesial and distal interproximal separation distance in upper the Denstply GAC® and American Ortontic® separators. The statistical analysis that was used the normality test and Chi square test. Results: Using the Denstply GAC® an interproximal separation distance of 0.15 mm, 0.21 mm and 0.31 mm was recorded at 24, 48 and 168 hours respectively. In the case of the America Ortodontic® separators, and interproximal separation distance of 0.17 mm, 0.20 mm and 0.29 mm was recorded at 24, 48 and 168 hours respectively. Conclusions: leaving the separators fou 48 hours is enough time to achieve the appropriate separation when adapting an orthodontic band.